Pengaruh Giro Wadiah dan Mudharabah terhadap Peningkatan Laba - Riyanto Riyanto; Arman Paramansyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2019)
This study was conducted to examine the effect of Giro Wadiah and Mudharabah deposits on the Net Profit of BRI Syariah. Research carried out by the unit of analysis Islamic Bank BRI in Bekasi. The method used in this research is descriptive method with data collection approach. Studies conducted through Primary data is data obtained directly from the research subjects in this case PT. Bank BRI Syariah and secondary data is data obtained from the research literature. The results showed that: (1) changes in demand deposits wadiah significant effect on Net profit in Syariah BRI (2) Changes in deposits mudaraba significant effect on net profit at Syariah BRI (3) Simultaneously Mudharabah Deposits Demand deposits and significant effect on the net profit at Syariah BRI.